A review of biochar in anaerobic digestion to improve biogas production: Performances, mechanisms and economic assessments. (December 2021) - Zhao, Weixin; Yang, Haizhou; He, Shufei; Zhao, Qingliang; Wei, Liangliang
Graphical abstract: Highlights: Biochar provided microbial habitat in AD system and enhanced biogas production. Excellent buffer capacity and accelerated electron transferring was observed. Biochar applications for biogas generation and purification were analyzed. Economic and environmental feasibilities of biochar addition in AD were evaluated. Abstract: Anaerobic digestion (AD) technology still faces some challenges including low methane productivity, instable operation efficiency and undesired refractory substances degradation. Biochar has recently been recognized as a promising alternative addition in AD process to enhance methane production. Based on VOSviewer analysis, this review presents a comprehensive summarizing of the applications, performances, and economies of biochar strategies in AD system. Firstly, typical production processes of biochar and its main characteristics including adsorption and immobilization ability, buffering ability and electron transfer ability were evaluated. Then, the applications of biochar in AD and its improving effects on biogas production/purification were summarized. Accordingly, the corresponding mechanisms of biochar addition in AD for digestion efficiency improvement were elucidated. Finally, the economic and environmental feasibilities of application biochar in AD, as well as prospective future studies were summarized. Through an overview of biochar in AD system, this paper aims to promote its widely practical applications.